'An altered view regarding the relationship between dreams and reality': Magic, politics and the comics medium in Alan Moore and Jacen Burrow's Providence. Issue 2 (1st December 2017) - Green, Matthew J. A.
Alan Moore reports that, through researching Providence, he 'became more fully acquainted with academic literary criticism' (Moore and Green 2016) and the extensive evidence of research throughout the series supports this claim. In this article, I argue that Providence uses the comics form to assert the value of humanities research and of the arts more broadly, and to educate its audience in reading and research practices (some of which are more providential than others). My focus is on the relationships between imagination and the historical realities of readers; while the latter are not detailed at length, the discussion does map onto the real world of Brexit, the aftermath of the 2016 US Presidential election and austerity politics because Moore's underlying premise is that it is possible to trace the origins of our contemporary moment through the societal anxieties encoded in Lovecraft's fiction. The analysis combines key concepts from adaptation studies with the theoretical model of the comics system proposed by Thierry Groensteen; moreover, it both draws upon and extends Brian McHale's work on metafiction to suggest ways of extending Groensteen's model in order to better understand the way in which Providence uses the comics medium to put into practice his hopes concerning the world-altering potential of art and scholarship.